Konseling Tentang Teknik Menyusui Yang Baik dan Benar Pada Ibu Post Partum di Kabupaten Bulukukmba - Husnul Khatimah; Sumarni Sumarni; Kurniati Akhfar; Nurul Hidayah Bohari (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Breastfeeding is the process of giving milk to infants or small children with breast milk (ASI) from the mother's breast. Breast milk is a type of food that is sufficient for all elements of a baby's physical, psychological, social and spiritual needs. Breast milk contains nutrients, hormones, immune elements, growth factors, anti-allergic and anti-inflammatory. Anti-infective substances contained in breast milk help protect babies against disease. So the purpose of this activity is to increase knowledge and skills about good and correct breastfeeding techniques for post partum mothers and to motivate mothers to give exclusive breastfeeding. The method used is the provision of accurate and updated information about breastfeeding and activities carried out in Paenre Lompoe Village, Bulukumba Regency. The main target in this community service is post partum mothers, totaling 20 people. The results of the community service carried out illustrate that there is an increase in knowledge and attitudes of post partum mothers regarding good and correct breastfeeding techniques